2006
DOI: 10.1097/01.mlg.0000184581.67185.6e
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nonabsorbable Packing in Middle Meatus after Sinus Surgery

Abstract: NAP in the MM for 5 days significantly reduced the extent of adhesions in MM compared with saline irrigation alone. NAP did not cause additional discomfort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
88
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(90 citation statements)
references
References 23 publications
0
88
0
2
Order By: Relevance
“…1268 Only CD gel, Merocel R , and Sepragel R were shown to confer any advantage over not packing at all, with both showing lower adhesion rates in their active treatment arms. 1268,1287 CD gel was also shown, in another RCT, to be associated with significantly larger sinus ostial sizes at 3 months, although this study did not report any difference in adhesion rates between treated and untreated cavities. 1292 A small noncontrolled study by Kim et al 1282 suggests that gloving the Merocel R pack prior to insertion may further reduce its postoperative adhesion rate; however, this finding has yet to be validated in a controlled study.…”
Section: Xd5 Surgical Principles/techniques: Use Of Packingmentioning
confidence: 52%
See 1 more Smart Citation
“…1268 Only CD gel, Merocel R , and Sepragel R were shown to confer any advantage over not packing at all, with both showing lower adhesion rates in their active treatment arms. 1268,1287 CD gel was also shown, in another RCT, to be associated with significantly larger sinus ostial sizes at 3 months, although this study did not report any difference in adhesion rates between treated and untreated cavities. 1292 A small noncontrolled study by Kim et al 1282 suggests that gloving the Merocel R pack prior to insertion may further reduce its postoperative adhesion rate; however, this finding has yet to be validated in a controlled study.…”
Section: Xd5 Surgical Principles/techniques: Use Of Packingmentioning
confidence: 52%
“…1274,1291 Both studies were small in number, however, and did not use validated pain scoring systems. Bugten et al 1287 also reported no significant difference in pain scores between patients packed bilaterally with Merocel R and those left unpacked, although a patient self-controlled study has not yet been performed to validate this observation. Several RCTs have directly compared pain and comfort levels of packing using absorbable vs nonabsorbable materials.…”
Section: Xd5 Surgical Principles/techniques: Use Of Packingmentioning
confidence: 96%
“…6 Several studies that looked at delayed postoperative bleeding in the weeks following FESS failed to show a significant difference for Merocel, CMC, MeroGel, and Floseal dressings. 8,9,11,13 Visual analog scale scores for bleeding on postoperative day 1 were reduced by MPH compared with control (22.5 vs 39; P < .001). However, the clinical relevance of 16.5 points on this 0-100 scale is uncertain (a score of 50 meant bleeding requiring occasional change of drip pad), and no other time points showed significant findings.…”
Section: Discussionmentioning
confidence: 75%
“…The single study evaluating the nonabsorbable dressing Merocel found a significant improvement in synechiae (RR, 0.21 [95% CI, 0.10-0.44]). 13 Subgroup analysis pooling data from the 3 studies evaluating absorbable dressings failed to show a significant reduction (P = .44). 8,10,12 Of the absorbable dressings, Chitosan gel resulted in less synechiae formation than no dressing (RR, 0.17 [95% CI, 0.04-0.69]).…”
Section: Discussionmentioning
confidence: 85%
“…have been tried in order to widen middle meatus and ethmoidectomy cavity. [13,14] These measures share a common role to keep away the denuded mucosal surfaces of the lateral side of the middle turbinate and ethmoid cavity. In this study, we aimed to use Sepragel ® sinus (Hylan B) with the same goal.…”
Section: Discussionmentioning
confidence: 99%